(untitled) (Sustainability in Debate, 2023)
Institutions and their different management and governance configurations are increasingly related to the environmental changes experienced on the planet. Therefore, this study aims to conduct a political and institutional review of biodiversity within the Brazilian federal government. To do so, we use the Political and Institutional Review - PIR to assess the strengths and weaknesses of biodiversity-related policies and institutions as part of the Biofin methodology. The study raised the main elements of the normative and institutional landscape that guided biodiversity conservation actions at the federal level between 2000 and 2019. The results showed that in this period, at least 21 norms and about 195 instruments were provided in federal legislation to meet the National Biodiversity Strategy and Action Plan – NBSAP. However, most of the budgetary actions carried out by the management bodies of biodiversity policies at the federal level distort the guidelines in these listed norms, along with the observed reduction in budget allocation for the Ministry of the Environment and biodiversity actions in other ministries. These elements seem to point to reduced prioritisation for biodiversity conservation at the federal level in Brazil over the 20 years analysed.